A Case of the Perinatal Form Hypophosphatasia Caused by a Novel Large Duplication of the ALPL Gene and Report of One Year Follow-up with Enzyme Replacement Therapy - Bülent Hacıhamdioğlu; Gamze Özgürhan; Catarina Pereira; Emre Tepeli; Gülşen Acar; Serdar Cömert (Galenos Yayincilik, 2019)
Hypophosphatasia (HPP) is a rare disease caused by mutations in the ALPL gene encoding tissue-non-specific isoenzyme of alkaline phosphatase (TNSALP). Duplications of the ALPL gene account for fewer than 1% of the mutations causing HPP. It has been shown that asfotase alfa enzyme replacement treatment (ERT) mineralizes the skeleton and improves respiratory function and survival in severe forms of HPP. Our patient was a newborn infant evaluated for respiratory failure and generalized hypotonia after birth. Diagnosis of HPP was based on low-serum ALP activity, high concentrations of substrates of the TNSALP and radiologic findings. On day 21 after birth, ERT using asfotase alfa (2 mg/kg three times per week, subcutaneous injection) was started. His respiratory support was gradually reduced and skeletal mineralization improved during treatment. We were able to discharge the patient when he was seven months old. No mutation was detected in the ALPL gene by all exon sequencing, and additional analysis was done by quantitative polymerase chain reaction (qPCR). As a result, a novel homozygote duplication encompassing exons 2 to 6 was detected. Early diagnosis and rapid intervention with ERT is life-saving in the severe form of HPP. qPCR can detect duplications if a mutation cannot be detected by sequence analysis in these patients.